Alternative fuel production from waste plastics and their usability in light duty diesel engine: Combustion, energy, and environmental analysis. (15th February 2023) - Mohan, Revu Krishn; Sarojini, Jajimoggala; Rajak, Upendra; Verma, Tikendra Nath; Ağbulut, Ümit
Abstract: Green biofuels have long been touted as a potential solution to society's reliance on fossil fuels and pollution emission problems. Commercially available renewable fuels like waste plastics oil alternative (P) made from waste plastic oil could take the place of fossil fuels, especially in diesel engines. Binary alternatives and diesel blends that partially replace diesel can be used in diesel engines without requiring major modifications. A four-stroke diesel engine used in the experiment was fed waste plastics oil alternative (up to 40% volumetric content), and diesel (D) mixes. Each binary blend is stabilised by a volumetric concentration and is composed of varying oil proportions. The investigations, therefore, relate partial diesel replacements to assessments of engine performance and mix combustion under various load conditions (25–100%), speeds (1200–1800 rpm), and compression ratios (15–19). Results showed that alternative-diesel mixtures up to 40% can still operate reliably. Thermal efficiency was somewhat lower than for diesel which was 100%. The experiment revealed higher fuel use, smoke, and NO emissions. The conclusion of the present research states that waste product oils can compete with fossil fuels in terms of engine performance, combustion, and emission characteristics when utilized in light-duty engines. Highlights: Waste to energy concept was handled in the paper. Energy recovery was provided from the waste plastics. Detailed combustion, performance, and emission characteristics were conducted. Injection timing effects affected the engine behaviours. Results were promising in terms of waste management.